Integrated transcriptome and metabolome analysis reveals the anthocyanin biosynthesis mechanisms in blueberry (Vaccinium corymbosum L.) leaves under different light qualities - Zhang, Jiaying; Li, Shuigen; An, Haishan; Zhang, Xueying; Zhou, Boqiang (Frontiers in Plant Science, 2022)
Blueberry (Vaccinium corymbosum L.) is a popular fruit with an abundance of anthocyanins in its leaves and fruits. Light is one of the pivotal environmental elements that affects plant growth and development, but the regulatory mechanism between lighting quality and anthocyanin formation is poorly understood. To reveal the potential pathway controlling anthocyanin biosynthesis in blueberry leaves, the effects of white (control), blue (B), red (R), and red/blue (60R/40B) light on blueberry growth were investigated, and an integrated transcriptome and metabolome analysis was performed. The results indicate that the anthocyanin content was significantly improved by the blue and red/blue light when compared with white light, whereas there was a significant reduction in the photosynthetic capacity of blueberry leaves under the blue light, showing an inverse trend to that of anthocyanin accumulation. Transcriptomic analysis was conducted and resulted in the de novo assembly of 134,709 unigenes. Of these, 22 were differentially expressed genes (DEGs) that participate in the anthocyanin biosynthesis pathway, with the majority being significantly up-regulated under the blue light treatment. Most of the photosynthesis-related genes that were down-regulated were expressed during anthocyanin accumulation. Targeted metabolome profiling identified 44 metabolites associated with anthocyanin biosynthesis in the leaves. The contents of most of these metabolites were higher under blue light when compared with the other light conditions, which was consistent with the transcriptome results. The integrated transcriptome and metabolome analysis suggested that, under blue light, leucoanthocyanidin dioxygenase (LDOX), O-methyltransferase (OMT), and UDP-glucose flavonoid glucosyltransferase (UFGT) were the most significantly expressed, and they promoted the synthesis of cyanidin (Cy), malvidin (Mv), and pelargonidin (Pg) anthocyanidins, respectively. The expression levels of dihydroflavonol 4-reductase (DFR) and OMT, as well as the accumulation of delphinidin (Dp), peonidin (Pn), and petunidin (Pt), were significantly increased by the red/blue light. This study identified the candidate genes and metabolites involved in anthocyanin biosynthesis in blueberry, which would provide a theoretical basis for elucidating the possible underlying regulatory mechanism of anthocyanin biosynthesis of V. corymbosum.